2021
DOI: 10.1098/rspb.2020.3107
|View full text |Cite
|
Sign up to set email alerts
|

Social network architecture and the tempo of cumulative cultural evolution

Abstract: The ability to build upon previous knowledge—cumulative cultural evolution—is a hallmark of human societies. While cumulative cultural evolution depends on the interaction between social systems, cognition and the environment, there is increasing evidence that cumulative cultural evolution is facilitated by larger and more structured societies. However, such effects may be interlinked with patterns of social wiring, thus the relative importance of social network architecture as an additional factor shaping cum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 43 publications
3
48
0
Order By: Relevance
“…Our results also complement recent modelling and empirical research suggesting modular networks have minimal effect on the spread of social information (Cantor et al 2021 ; Laker et al 2021 ). For example, Laker et al ( 2021 ) showed that the transmission of novel foraging information was not impacted by the modularity of network structure in domestic fowl chicks Gallus gallus domesticus .…”
Section: Discussionsupporting
confidence: 90%
“…Our results also complement recent modelling and empirical research suggesting modular networks have minimal effect on the spread of social information (Cantor et al 2021 ; Laker et al 2021 ). For example, Laker et al ( 2021 ) showed that the transmission of novel foraging information was not impacted by the modularity of network structure in domestic fowl chicks Gallus gallus domesticus .…”
Section: Discussionsupporting
confidence: 90%
“…Complementing this work, Smolla and Akçay ( 2019) recently showed that networks and culture may co-evolve, with environments that select for specialist knowledge resulting in sparse connectivity patterns, such that individuals are repeatedly exposed to the same information and increase their depth of expertise, while environments that select for generalist knowledge result in dense connectivity patterns, for complementary reasons. Other recent results from (Cantor et al, 2021) suggest that the relationship between network structure, population size, and diffusion mechanisms are highly complex: networks that perform best in terms of cumulative cultural evolution in one context may perform worst in another.…”
Section: Discussionmentioning
confidence: 99%
“…Sociocultural evolution is typically understood as affecting behavioral traits expressed in a human population, which we can reproduce in silico to measure their emergent effect. For example, perhaps cultural evolution can amplify small individual biases (Thompson et al, 2016), perhaps naive social learning (Henrich & Boyd, 1998) and sparse patterns of socio-cultural transmission (Cantor et al, 2021;Migliano et al, 2020) facilitate cumulative cultural evolution, or perhaps between-group conflict drives the evolution of unequal or xenophobic human groups (Makowsky & Smaldino, 2016). For the model to generate legible results, it needs to have clearly defined, easily measurable / manipulable parameters from which we can extract clear effects through statistical inference.…”
Section: -Social Transmission Without Cognitive Agencymentioning
confidence: 99%